The efficiency of national zakat organizations management using data envelopment analysis - Wahyuni, Ikka Nur (Journal of Islamic Economics Lariba, 2016)
This study is aimed to investigate the efficiency level of national organization of Zakat management (OPZ) in 2013 by applying Data envelopment analysis method and intermediation as well as production approach. The result shows that national zakat organizations management,Â  Badan Amil Zakat Nasional, Dompet Dhuafa, Laziz Nahdlatul Ulama, and Pos Keadilan Peduli Ummat (PKPU), have efficient performance based on the efficiency measurement. Baznas and Dompet Dhuafa, based on the production approach measurement, showing an inefficiency in term of operational cost variable, personnel cost, ziswaf socialization cost, and the distributed ziswaf fund.